Sustainable sport management : running an environmentally, socially and economically responsible organization - Chernushenko, David (United Nations Environment Programme OntarioCA, 2001)
Acknowledges the challenges and pressures that sports managers face regarding the environment. Defines sustainability and presents it as the new and viable management approach. Suggests strategies which managers can employ to help staff, volunteers, and stakeholders to embrace this change. Looks at issues including: waste management, protection of athletes and spectators. Includes case studies of sports organizations that have integrated sustainability into their management strategy.